ANALISIS KUALITAS AIR DAN STRATEGI PENGENDALIAN PENCEMARAN DI DANAU BATUR MENGGUNAKAN ANALISIS FORCE-FIELD - Ni Komang Ayu Septiani; I Wayan Budiarsa Suyasa; I Nyoman Rai (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2022)
Batur is the largest lake in Bali which has the potential to experience pollution due to the high activity in the body and the surrounding environment. This condition indicates the need for serious management efforts to maintain water quality. This study aims at analysing the water quality, status of the water quality of Lake Batur and also formulate a strategy for controlling water pollution in Lake Batur. The water sample analysis method was carried out in two ways, namely in situ method and laboratory testing. The feasibility level of the results was matched with the Class 1 Water Quality Standard based on the Bali Governor Regulation number 16 of 2016, for the status of the water quality determined by the Pollution Index Method according to the Decree of the State Minister of the Environment No. 115 year 2003. In determining the control strategy, the force field analysis method was applied. The results of the study, there were several parameters that exceeded the quality standard ranging from 18.33-23 mg/l. In addition, the DO content at some points was also not classified as lightly polluted where the highest IP value is Brother with a value of 2.07. The pollution control strategy of Lake Batur produced based on force field analysis was increasing innovative socialization to the community, increasing the promotion of Lake Batur conservation, providing training and entrepreneurial skills as well as providing small-scale business capital assistance, synergizing government policies and programs and forming a pollution control unit. Keywords: water quality; pollution index; control strategy.